The Effect of Lead Time toward Supply Control at Paku Payung Club - Diki Triadi Setiawan; Nurhasanah (Jurnal Ilmu Sosial Politik dan Humaniora (JISORA), 2022)
The background of this research is that the company experienced delays in receiving ordered goods due to several reasons, namely the limited activity of suppliers in producing ordered goods, and also delays in transportation in the delivery of goods orders resulting in delays in the supply of goods to the company. The lead time that the company has estimated is 168 hours; due to limited transportation, receiving orders has been delayed, especially in July 2020, which was 192 hours, and in March 2021, which was 144 hours. This study aims to determine the effect of lead time on inventory control of hijab label accessories at Paku Payung Club (PPC). Inventory control is one of the management functions that are very important to determine the level of inventory that must be maintained so that inventory does not run out of goods or otherwise experience excessive inventory. The research was conducted based on data on lead time and company control from July 2020 to July 2021. The research method used is an associative descriptive research method, then the type of quantitative data and ratio scale. Then it is processed using the classical assumption test, regression test, simple correlation test, coefficient of determination test, partial significant hypothesis test (t-test), and simultaneous hypothesis test (f test). The results show that there is an effect of lead time on inventory control at Paku Payung Club, with a correlation coefficient that has a powerful influence. This research is expected to be input for the Paku Payung Club business manager in production planning thus that the business can run effectively and efficiently. Keywords: Lead time; Inventory Management; Inventory Control